[Okta Webinar] Learn how to a build a cloud-first strategyRegister Now

x
  • Status: Solved
  • Priority: Medium
  • Security: Public
  • Views: 712
  • Last Modified:

algebra question expression for F(X)

I'm trying to understand how to get this answer.  
If f(3b-1) = 9b-1, find one possible expression for f(x).  The sample answer is f(x)=3x+2.

Not sure the logic to get to the answer.  Thanks for any help.  I apologize if this is the wrong forum.
0
javierpdx
Asked:
javierpdx
1 Solution
 
abbrightCommented:
If you set x=3b-1 then b=(x+1)/3. Now replace b on the every occasion in the equation:
So f(x)=9* ((x+1)/3) -1=3(x+1)-1=3x+2
0
 
javierpdxAuthor Commented:
Thanks.
0

Featured Post

Concerto's Cloud Advisory Services

Want to avoid the missteps to gaining all the benefits of the cloud? Learn more about the different assessment options from our Cloud Advisory team.

Tackle projects and never again get stuck behind a technical roadblock.
Join Now